2021
DOI: 10.32535/ijafap.v4i1.1036
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Good Corporate Governance in Enhancing the Performance of Village Credit Institutions

Abstract: Good corporate governance is corporate governance that explains the relationship between all interested parties in a regulated and organized business. The principles of good corporate governance should be also applied by village credit institutions to improve their performance. This research aims to examine and obtain empirical evidence of the influence of good corporate governance principles, including transparency, accountability, responsibility, independence, and fairness, on the performance of village cred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
1
0
Order By: Relevance
“…The goal of this method is to facilitate effective and efficient management to provide long-term success for an organization. Implementing good corporate governance will prevent mistakes in decision making and self-beneficial actions which significantly increase the value of company (Putra, Sunarwijaya, & Gunadi, 2021) Therefore, it is about the Board of Commissioners action and to determine organizational values.…”
Section: Good Corporate Governancementioning
confidence: 99%
“…The goal of this method is to facilitate effective and efficient management to provide long-term success for an organization. Implementing good corporate governance will prevent mistakes in decision making and self-beneficial actions which significantly increase the value of company (Putra, Sunarwijaya, & Gunadi, 2021) Therefore, it is about the Board of Commissioners action and to determine organizational values.…”
Section: Good Corporate Governancementioning
confidence: 99%
“…Several studies have shown that good governance practices can lead to many positive outcomes, including better delivery of public services, increased public satisfaction and trust in government, reduced corruption and inefficiency, increased economic growth and development, and more excellent social stability (Ambarwati et al, 2019;Putra et al, 2021). Therefore, district/city governments must prioritize implementing good governance practices and principles.…”
Section: Introductionmentioning
confidence: 99%
“…The LPD performance is believed to illustrate the extent to which its success in achieving its goals. Also, it deals with how the LPDs achieve their objectives (Putra, Sunarwijaya, & Gunadi, 2021). The more successful it is, the more benefits it provides to customary villages since some of the profits can be used to fund customary activities and increase the loan ceiling.…”
Section: Introductionmentioning
confidence: 99%